Level of education associated with ophthalmic diseases: the Beijing eye study - Xu, Liang; Wang, Ya Xing; Jonas, Jost B. (Graefe's archive for clinical and experimental ophthalmology, 2010)
To determine associations between educational level and ophthalmic diseases in Chinese.